Sosialisasi Dampak Gadget Bagi Anak-Anak Tingkat Dasar di Desa Jaya Mulya Semendawai Suku III - Resti Septikasari; Ratih Purnama Pertiwi; Sri Enggar Kencana Dewi; Tri Ratna Dewi; Nor Kholidin; Imam Rodin (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasing use of electronic devices, specifically gadgets, among elementary school children has caused various problems, such as addiction, decreased social interaction, health problems, and decreased concentration in learning. These problems involve not only children but also objects and things around them, as well as parents in managing them. Gadget use is not just a matter of quantity that exacerbates this condition. As a solution, the community service team held a socialization focused on improving healthy digital literacy through counseling, interactive discussions, and practical simulations. Results achieved included increased knowledge about the risks of excessive gadget use, increased collective awareness in limiting usage time, and the formation of practical guidelines for healthy gadget use in school and family environments. The results of the activity were documented in the form of a scientific article published in the community service journal as an academic contribution. Overall, the activity has gone according to plan in terms of planning, implementation, and partner involvement. Active participation of participants was evident in the enthusiasm in the discussions and the school's commitment to continuously monitoring gadget use. Thus, this program is expected to have a long-term positive impact in shaping wise behavior in using technology among elementary school children.